Moral distress among healthcare students: an integrative review (Research, Society and Development, 2020)
Objective: to identify the scientific production about moral distress among healthcare students. Method: an integrative review that included original articles indexed in the Medical Literature Analysis and Retrieval System Online (MEDLINE), Cumulative Index to Nursing and Allied Health Literature (CINAHL) databases and in the PUBMED portal without time and language restrictions. The analysis of the results occurred in a descriptive way, in three analytical categories. Results: 32 articles were selected, published in international journals, the largest number was in the journal Nursing Ethics. Regarding the level of evidence, 22 qualitative and descriptive studies were in evidence stratum IV and 10 articles between reports of experiences and articles of reflection at level of evidence V. After analysis, three thematic categories were elaborated: Moral distress in the training environment of Health area; Coping with Moral distress: possible repercussions; Academic training: future directions for facing Moral distress. Conclusion: the articles portray that Moral Suffering occurs throughout the career of health professionals, including among students. Situations that cause Moral distress in students must be faced by all undergraduate courses in order to maintain the well-being of students and ensure quality academic education in health.